Konsep Nafkah Menurut Muhammad Syahrur dan Kompilasi Hukum Islam - Hidayat, Riyan Erwin; Fathoni, Muhammad Nur (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
Livelihood is meeting the needs of food, shelter, and the wife's treatment, and it is clear that a husband is obliged to provide maintenance to his wife. Based on the law, maintenance is a husband's obligation to his wife that must be met in the form of household needs in accordance with the husband's ability. However, at present, there are various disputes regarding what conditions are included in subsistence, especially in terms of types of subsistence. Therefore, this research is a study that discusses the concept of living according to Muhammad Syahrur and the Compilation of Islamic Law. About how the relevance of his thoughts. To know the relevance of Muhammad Syahrur and the Compilation of Islamic Law regarding maintenance. The type of research used is library research, so the research is not a "trial and error" activity (a step of activity carried out to try and try again). Based on the explanation of Law Number 1 of 1974 concerning marriage and KHI, it can be concluded that the husband is obliged to provide maintenance for his wife because maintenance is the second obligation of the husband to his wife after the husband gives the dowry to the wife.